PENGARUH LABA AKUNTANSI, KOMPONEN ARUS KAS, PRICE EARNINGS RATIO, DAN DIVIDEND YIELD TERHADAP RETURN SAHAM - Mastu’ah Mastu’ah; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to analyze the effect of accounting earnings, cash flow components, price earnings ratio, and dividend yield on stock returns during the period 2015-2017. The variables examined in this study were accounting earnings, cash flow components, price earnings ratio and dividend yield as independent variables, stock returns as the dependent variable. The research method used is descriptive statistical method. By testing verification using multiple regression. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the period 2015-2017. The data used is secondary data, namely the annual report of the company that was sampled in the study. The research sample was 31 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017 which were taken using the Purposive Sampling method. The results of this study indicate that operating cash flows, funding cash flows, price earnings ratios and dividend yields positively influence stock returns, but accounting earnings and investment cash flows do not have a positive effect on stock returns.KEYWORDS: Accounting Profit, Operating Cash Flow, Investment Cash Flow, Funding Cash Flow, Price Earnings Ratio, Dividend Yield, Stock Return.